Diffusion-Weighted MR Neurography of the Brachial Plexus: A literature review (Research, Society and Development, 2021)
The brachial plexus is formed by the union of the ventral branches of the C5-T1 roots and, occasionally, of the C4 and T2 roots, where the most frequent causes of traumatic injuries involve traffic accidents, mainly collisions by motorcycles. The precise diagnosis of the level of the lesion and degree of impairment is of fundamental prognostic importance and determines the therapeutic approach for each clinical case. In order to evaluate the limitations and perspectives of the application of diffusion neurography in MRI for generating brachial plexus images in different pathological situations, a systematic bibliographic survey was carried out until the year 2021 in the PubMed, Cochrane and Science Direct database. The exclusion criteria of which were publications that did not report an association between brachial plexus and diffusion sequence on magnetic resonance imaging. The literature review points out that the diffusion technique (DWI) by magnetic resonance imaging (MRI) demonstrated satisfactory selective images for anatomical visualization of the brachial plexus and high signal intensity of the nerve roots and peripheral nerves, providing details of the topography and describing the long trajectory of the brachial plexus, allowing a more accurate and safe evaluation when compared with conventional planar images. The studies demonstrated the importance of diffusion neurography in MRI as a promising method for visualizing peripheral nerves in the brachial plexus region.